Dampak Perkebunan Kelapa Sawit Terhadap Kondisi Sosial Ekonomi Masyarakat Desa Balanti Kabupaten Hulu Sungai Selatan - Normalinda, Siti; An'Amta, Dimas Asto Aji (Prodi Sosiologi FISIP ULM, 2024)
The presence of an industry will always have an impact on society, both positive and negative impacts. The research aims to determine the impact of the presence of oil palm plantations on the socio-economic conditions of the Balanti Village community. The research uses qualitative research methods with a descriptive approach. The data collection techniques used observation, interviews and documentation. Data were analyzed by means of data reduction, data presentation, and drawing conclusions. The theory used is the theory of social change according to Kingsley Davis (Soekanto, 2015). The research results show that the presence of oil palm plantations in Balanti Village has an impact on the socio-economic impact of the community. The presence of plantations has an impact on increasing income and permanent income. Before the establishment of oil palm plantations, the community's main job was as farmers and since the presence of oil palm plantations, the community has been able to improve their housing, and their level of education has increased. The presence of oil palm plantations does not have much influence on the social life of the community, for example, social interaction and the community culture of mutual cooperation have not disappeared but have changed, especially in terms of time. With so many people working on oil palm plantations, most community meetings are only held in the afternoon. It is hoped that companies will always make a big contribution in supporting the economic progress of village communities and it is hoped that the community will not ignore the habits that exist in the community.